2022
DOI: 10.3389/fmicb.2022.967565
|View full text |Cite
|
Sign up to set email alerts
|

Responses of soil fungal communities and functional guilds to ~160 years of natural revegetation in the Loess Plateau of China

Abstract: Natural revegetation has been widely confirmed to be an effective strategy for the restoration of degraded lands, particularly in terms of rehabilitating ecosystem productivity and soil nutrients. Yet the mechanisms of how natural revegetation influences the variabilities and drivers of soil residing fungal communities, and its downstream effects on ecosystem nutrient cycling are not well understood. For this study, we investigated changes in soil fungal communities along with ~160 years of natural revegetatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 90 publications
0
3
0
Order By: Relevance
“…Firstly, Q 10 is expected to vary with changes in temperature (Davidson & Janssens, 2006), so the exploration of Q 10 along a temperature gradient could further reveal the response characteristics of decomposition to warming under fluctuating background temperatures. Secondly, only bacterial communities were considered in this study, whereas fungi may have a stronger effect than bacteria in utilizing refractory organic carbon (e.g., lignocelluloses and humus) by producing a wide range of extracellular enzymes (Alster et al., 2018; Peay et al., 2008; Yang et al., 2022). Therefore, we encourage the incorporation of multiple microbial taxonomic groups into studies of carbon decomposition and its temperature sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, Q 10 is expected to vary with changes in temperature (Davidson & Janssens, 2006), so the exploration of Q 10 along a temperature gradient could further reveal the response characteristics of decomposition to warming under fluctuating background temperatures. Secondly, only bacterial communities were considered in this study, whereas fungi may have a stronger effect than bacteria in utilizing refractory organic carbon (e.g., lignocelluloses and humus) by producing a wide range of extracellular enzymes (Alster et al., 2018; Peay et al., 2008; Yang et al., 2022). Therefore, we encourage the incorporation of multiple microbial taxonomic groups into studies of carbon decomposition and its temperature sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we examined the microbial communities in S. chinensis from different geographical locations, of different varieties, and in compartments with different ecological niches. The diversity and homogeneity of soil microbial community structure affect ecosystem stability; improve the ability of crops to respond to changes in the soil microbiological environment, particularly to pathogenic microorganisms; and enhance disease resistance of crops ( Yang S. et al, 2022 ; Yang J. et al, 2022 ). The alpha-diversity analysis showed that the diversity and homogeneity of the microbial community were higher than those of the microbial community in the rhizospheric soil samples of S. chinensis and showed a highly significant relationship between different compartments.…”
Section: Discussionmentioning
confidence: 99%
“…The Actinobacteriota includes many members of plant growth-promoting bacteria ( Dawkins and Esiobu, 2018 ); these members can degrade plant residues in soil and convert them into an inorganic form that is more readily absorbed by plants ( Wang X. et al, 2022 ; Wang Q. et al, 2022 ). Basidiomycota , a significantly enriched group of related fungi in leaves, can degrade low-quality substrates and recalcitrant lignin and lignocellulosic matrices ( Yang S. et al, 2022 ; Yang J. et al, 2022 ). Based on the random forest analysis, we identified marker species at the genus level in different S. chinensis samples.…”
Section: Discussionmentioning
confidence: 99%